2018
DOI: 10.1075/ml.18016.khw
|View full text |Cite
|
Sign up to set email alerts
|

Imageability, familiarity, and age of acquisition ratings for Arabic abstract nouns, abstract verbs and adjectives

Abstract: To date, normative psycholinguistics research has mainly focused on establishing norms for producing databases for concrete words using standardized pictures, while abstract words have been subject to much less attention. Understandably, the fact that the first can be represented visually helps in formulating picture-naming tasks to elicit verbal identification for pictures representing nouns and verbs, which greatly contributes to language experiments in both theoretical and clinical studies. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…These observations support the view that while imagery and concreteness are strongly correlated, they are not identical constructs (Connell & Lynott, 2012;Dellantonio et al, 2014;Kousta et al, 2011;Richardson, 1975). Furthermore, the observation that several concrete words (e.g., κέδρος/cedar, βίσωνας/bison, υάκινθος/hyacinth) exhibit lower imagery scores supports previous findings indicating that various other variables (e.g., familiarity and subjective frequency) influence how words are processed (Boles, 1983;Guasch et al, 2016;Khwaileh et al, 2018;Lima & Buratto, 2021;Warriner et al, 2013;Yee, 2017). For example, all participants rated the word 'κέδρος/cedar' as concrete, since they recognized it as a type of tree.…”
Section: Discussionsupporting
confidence: 83%
“…These observations support the view that while imagery and concreteness are strongly correlated, they are not identical constructs (Connell & Lynott, 2012;Dellantonio et al, 2014;Kousta et al, 2011;Richardson, 1975). Furthermore, the observation that several concrete words (e.g., κέδρος/cedar, βίσωνας/bison, υάκινθος/hyacinth) exhibit lower imagery scores supports previous findings indicating that various other variables (e.g., familiarity and subjective frequency) influence how words are processed (Boles, 1983;Guasch et al, 2016;Khwaileh et al, 2018;Lima & Buratto, 2021;Warriner et al, 2013;Yee, 2017). For example, all participants rated the word 'κέδρος/cedar' as concrete, since they recognized it as a type of tree.…”
Section: Discussionsupporting
confidence: 83%
“…Lexical class was a major determinant of target-naming RTs in ASL picture naming. Action pictures were named more slowly than object pictures, as is found for spoken languages (Bates et al, 2003;Bayram et al, 2017;Khwaileh et al, 2018). Naming actions also yielded a higher number of alternative names, leading to poorer name consistency compared with naming objects.…”
Section: Lexical Classmentioning
confidence: 64%
“…Studies of picture naming in spoken languages have revealed potential differences between the mental representations of nouns (i.e., object names) and verbs (action names). These studies indicate that object names tend to be retrieved faster and with better agreement than action names (Bayram et al, 2017;Khwaileh et al, 2018;Mätzig et al, 2009;Szekely et al, 2005). This pattern holds even when the stimuli are matched for relative difficulty in terms of the target name (e.g., age of acquisition) and picturerelated properties (e.g., picture complexity) (Szekely et al, 2005).…”
mentioning
confidence: 86%
“…Most of the research on Arabic processing (Albustanji, 2009;Béland & Mimouni, 2001;Idrissi & Kehayia, 2004;Idrissi et al, 2002;Khwaileh, 2011;Khwaileh et al, 2014Khwaileh et al, , 2015Khwaileh, Mustafawi, Howard, & Herbert, 2016;Khwaileh et al, 2017;Khwaileh, Mustafawi, Herbert, & Howard, 2018;Khwaileh, Mustafawi, Howard, & Herbert, 2019;Mimouni et al, 1998Mimouni et al, , 1997 lack use of standardized material and response categorisation protocols for error analysis. The aim of this paper is to develop a linguistically informed and data-driven response categorisation protocol for language breakdown of the Arabic language.…”
Section: Aim and Scope Of This Papermentioning
confidence: 99%